Khusyuk dalam melaksanakan ibadah solat: peranannya dalam mencegah perkara keji dan mungkar / Muhammad Saiful Anuar Yusoff ... [et al.] - Yusoff, Muhammad Saiful Anuar; Che Mat, Azman; Mohd Saad, Muhammad Luqman Ibnul Hakım; Ismail, Mohd Khairul Anuar; Seman, Zawiah (2018)
Being steadfast (khusyuuk) is the most important element in achieving quality prayer. This study was conducted to investigate the roles of prayers which are performed with pure steadfastness in prayers as the prevention against ill manners (fahsya’ & mungkar). The research framework was constructed based on the Quran verse ordained by Allah in Al’ Ankabut: 45 “Indeed, prayer prohibits immorality and wrongdoing, and the remembrance of Allah is greater. And Allah knows that which you do.” Influence of two variables: steadfastness of the soul on steadfastness of the body on one another and on the respondents’ perception of avoiding ill manners was studied. 256 sets of data was collected from respondents who were the students of five Diploma and Degree programs at Universiti Teknologi MARA Kelantan. Data analysis was carried out using SmartPLS 3. The findings of the study revealed that steadfastness of the soul has positive impact on steadfastness of the body and the two variables also positively impacted respondents’ perception of avoiding ill manners. The study provides a guideline in shaping good disposition and manners (akhlaq) and preventing ill manners among students through the performance of prayers with pure steadfastness and submissiveness.